Language Minority Students in American Schools. - Adamson, H. D. (Hugh Douglas) (Lawrence Erlbaum Associates, 2005)
This work addresses questions of language education in the United States, focusing on how to teach the 3.5 million students in American public schools who do not speak English as a native language.